(untitled) (The Review of Diabetic Studies, 2024)
Chronic pain affects approximately 50-60% of older adults living in community settings and up to 80% of those in long-term care facilities, significantly impacting quality of life, functional independence, and psychological well-being. This comprehensive review examines evidence-based nursing interventions for managing chronic pain in the geriatric population. A systematic literature search was conducted across multiple databases including PubMed, CINAHL, and Cochrane Library, focusing on peer-reviewed studies published between 2018 and 2024. The review synthesizes findings on pharmacological management, non-pharmacological interventions, multimodal approaches, and the role of nurses in comprehensive pain assessment and management. Results indicate that multimodal approaches combining pharmacological and non-pharmacological interventions demonstrate superior outcomes compared to single-modality treatments. Nurses play a pivotal role in pain assessment, patient education, advocacy, and coordination of interdisciplinary care. Barriers to effective pain management include ageist attitudes, concerns about opioid dependency, communication challenges, and insufficient pain education among healthcare providers. The review concludes with recommendations for nursing practice, education, and future research directions to enhance chronic pain management in older adults.